An Introduction to Human Resource Management - Wilton, Nick (Los Angeles ; London : SAGE Publications Ltd, 2022)
"Reflecting the global nature of the workplace, this is a concise introduction to the world of human resource management that goes beyond a prescriptive, how-to approach and prepares you for the issues and dilemmas you may face in your HR career. Includes new discussions on the impact of Black Lives Matter on HR, the effect of Covid-19 on recruitment and on the mental health of employees, and post-Brexit points-based immigration. Suitable for anyone studying HRM - as part of an undergraduate or postgraduate degree, or on a specialist program of study." -- provided by publisher.
Previous edition: 2019.
Includes bibliographical references (pages 472-513) and index.
Keywords: Personnel management; Personnel departments -- Employees